Conflict as a component of adolescent development - Zhumankulova, Yerkyn; Orazaeva, Gulzhan; Salgarayeva, G. (Pedagogy and Psychology, 2024)
The article discusses the influence of intrapersonal conflict on the formation of asocial behavior of teenagers. Attention is paid to the specific behavior of adolescents with special needs who are studying in conditions of inclusion. Ways of overcoming asocial behavior, through the work of a psychologist with teenager, family are considered. The article provides a brief analysis of the studies of conflict and the role of the family in the prevention of antisocial behavior of adolescents. An analysis was made of statistical data on offences committed by children in the Republic of Kazakhstan and the number of families with low subsistence levels. Based on the results of the analyses, the article provides a comprehensive program of work with asocial teenagers and their families for the prevention and correction of asocial behavior.